2013
DOI: 10.1192/bjp.bp.111.106666
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and depression in adults: systematic review and meta-analysis

Abstract: Our analyses are consistent with the hypothesis that low vitamin D concentration is associated with depression, and highlight the need for randomised controlled trials of vitamin D for the prevention and treatment of depression to determine whether this association is causal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
443
6
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 657 publications
(531 citation statements)
references
References 56 publications
27
443
6
10
Order By: Relevance
“…This supports previous reviews findings of general hypovitaminosis D in this patient population with one review findings 59.14% and the other 65.3% (Belvederi Murri et al, 2013;Valipour et al, 2014, respectively) and suggests that on average over half of psychotic patients are deficient of vitamin D at any one time. This is in line with research in other areas suggesting that low vitamin D is also common in other mental health disorders such as depression and anorexia (Anglin et al, 2013;Veronese et al, 2015, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…This supports previous reviews findings of general hypovitaminosis D in this patient population with one review findings 59.14% and the other 65.3% (Belvederi Murri et al, 2013;Valipour et al, 2014, respectively) and suggests that on average over half of psychotic patients are deficient of vitamin D at any one time. This is in line with research in other areas suggesting that low vitamin D is also common in other mental health disorders such as depression and anorexia (Anglin et al, 2013;Veronese et al, 2015, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…The majority of these are centred on the ability of certain nutrients contained within FV to influence psychological well-being. While a number of nutrients such as n-3 PUFA (15) , vitamin B 12 (10) and vitamin D (16) have been studied with regard to psychological well-being, this review only focuses on nutrients that are found in FV, and which have shown promise in this regard.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…Although there is a variation in the prevalence of depression using different tools, mental health problems namely depression are health conditions that should not be overlooked. Its consequences include impairment in functional well-being and poorer quality of life (10,11) , physical distress and health problems (12) .A systematic review by Anglin et al (13) found an increased odds/risk of depression for the lowest v. highest vitamin D categories in cross-sectional studies (OR = 1·31; 95 % CI 1·0, 1·71) as well as cohort studies (hazard ratio = 2·21; 95 % CI 1·40, 3·49). Ecemis and Atmaca (14) found that quality of life was impaired in vitamin D-deficient and -insufficient premenopausal women.…”
mentioning
confidence: 99%